Axillocephalic arteriovenous graft: A new alternative for hemodialysis - (:unkn) unknown (My University, 2000)
Different types of vascular accesses are used for patients who need hemodialysis due to chronic renal failure. The most commonly used are arteriovenous fistulae (AVF) which can be classified as autogenic or prosthetic grafts. Prosthetic arteriovenous grafts can be placed into anatomic or, in complicated case, into extra-anatomic locations. In this paper, we present a patient who had the AVF operation four times and the femoral arteriovenous graft operation twice and we report an alternative hemodialysis access, 'axillocephalic graft interposition'.
Keywords: Arteriovenous graft; Chronic renal failure; Hemodialysis access